Abstract 12046: ARFI Ultrasound Elastography Measures Isovolumic Relaxation Time Constant for Assessment of Diastolic Function - Vejdani-Jahromi, Maryam; Freedman, Jenna; Joong-Kim, Young; Osborn, Jenna; Trahey, Gregg; Wolf, Patrick (Circulation (New York, N.Y.), 2016)
IntroductionDiastolic dysfunction is a leading cause of morbidity and mortality in heart failure. Assessment of diastolic function has been a challenging topic for many decades. One index of diastolic function is the isovolumic relaxation time constant (τ). This measurement is not used routinely in the clinic because it requires a left ventricular (LV) pressure catheter. Other noninvasive methods provide correlates of the time constant but do not measure the actual value. It has been shown recently that ultrasound elastography (Acoustic Radiation Force Impulse Imaging (ARFI)) can provide a temporal stiffness measurement of the myocardium during the cardiac cycle. The clinical value of the ARFI measured time course of softening has not been shown.HypothesisWe assessed the hypothesis that ARFI Elastography can be used to measure the isovolumic relaxation time constant of the LV.MethodsThis study was performed in eight isolated rabbit hearts in working mode. A pressure catheter was used to record the LV pressure simultaneously with ARFI. LV free wall ARFI measurements were recorded using an ultrasound probe. In order to extend the range of τ (tau) measurements, 3 of the subjects were subjected to ischemia (total of 11 measurements from 8 subjects).ResultsTau measured by ARFI was linearly related to the τ measurement derived from LV pressure with the slope of 0.92 and R = 0.90 indicating the near equivalence of the values. Mean ± SEM of τ derived from pressure and ARFI were 33.7 ± 6.4 ms and 34.8 ± 6.2 ms respectively.ConclusionsARFI ultrasound elastography can be used to measure the relaxation time constant of the left ventricle. This is the first time that τ has been measured directly using an ultrasound technique. ARFI measurements have the benefits of ultrasound imaging including noninvasiveness, cost efficiency and portability. Translation of this technique to transthoracic imaging in humans would provide an important screening measure of diastolic function.